ПРОБЛЕМИ ДІЯЛЬНОСТІ СУБ’ЄКТІВ ДЕРЖАВНОГО РЕГУЛЮВАННЯ СТАЛОГО РОЗВИТКУ УКРАЇНИ - Бурик, Зоряна Михайлівна (SUPREMANCE OF LAW, 2018)
The article deals with thepeculiarities of the organizational support of state management by regional development, the introduction of formal and informal institutions of the institutional environment. It was established that the organizational and institutional support of state regulation of sustainable development includes: the institute of the state, the institute of law, the market institute and the public institute. The main problems in the activity of the authorities in the process of development of sustainable development strategies are presented. It is proposed to create a special body - the Agency for Sustainable Development under the Cabinet of Ministers of Ukraine.
Keywords: institutional development; institutional support; institutional environment; sustainable development; state policy